ANALISA PENCITRAAN TERHADAP PERLUASAN MEREK SKH KOMPAS BAGI PEMBACA DI JAKARTA (KOMUNIKOLOGI : Jurnal Ilmiah Ilmu Komunikasi, 2019)
This study aims to find out whether the image of Kompas is required to obtain a brand (Expansion of Brands) for Readers in Jakarta specifically in South Jakarta. developments in information and communication technology, new media based online through the Kompas e-paper version. The results of this study indicate that Kompas has competitiveness against other companies, using strategies that can improve company relationships with Readers as an increase in motivation and loyalty from Readers. Keywords: imaging, expansion of brands, now COMPASS e-paper